Can off-task be on-track?. (May 2019) - Gargroetzi, Emma C.; Chavez, Rosa D.; Munson, Jen; Langer-Osuna, Jennifer M.; Lange, Kimiko E.
Collaborative learning requires a lot of talk. Although not all student talk may be related to the task at hand, some off-task talk is actually productive, as it enables students to negotiate how they will work together, gain attention of fellow group members, and draw others into joining the work. Emma C. Gargroetzi, Rosa D. Chavez, Jen Munson, Jennifer M. Langer-Osuna, and Kimiko E. Lange observed 4th-grade students working in groups on math exercises and saw multiple seemingly off-task conversations that, in fact, ended up bringing the group together. For example, students who were excluded used off-task talk to get others in the group to pay attention to them. Groups also used off-task talk to ensure that everyone in the group had a role in the solution. The authors offer guidelines for determining when to intervene when students engage in off-task talk .